Konsep Jarak Terdekat dalam Menghadap Kiblat - Siti Tatmainul Qulub (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Facing the Qibla is a legitimate requirement in the salat. In some recent astronomical literature mentioned that the meaning of the direction of Qibla is the closest distance to the Kaaba. In the literature books of fiqh as well as classical celestial sphere is not mentioned meaning Qibla direction as the closest distance to the Kaaba (Mecca). Qiblah word in the verse means